The quotable Kierkegaard - Kierkegaard, Søren, 1813-1855 (Princeton University Press, 2014)
"Why I so much prefer autumn to spring is that in the autumn one looks at heaven--in the spring at the earth."--Søren Kierkegaard. The father of existentialism, Søren Kierkegaard (1813-1855) was a philosopher who could write like an angel. With only a sentence or two, he could plumb the depths of the human spirit. In this collection of some 800 quotations, the reader will find dazzling bon mots next to words of life-changing power. Drawing from the authoritative Princeton editions of Kierkegaard's writings, this book presents a broad selection of his wit and wisdom, as well as a stimulating introduction to his life and work. Organized by topic, this volume covers notable Kierkegaardian concerns such as anxiety, despair, existence, irony, and the absurd, but also erotic love, the press, busyness, and the comic. Here readers will encounter both well-known quotations ("Life must be understood backward. But then one forgets the other principle, that it must be lived forward") and obscure ones ("Beware false prophets who come to you in wolves' clothing but inwardly are sheep--i.e., the phrasemongers"). Those who spend time in these pages will discover the writer who said, "my grief is my castle," but who also taught that "the best defense against hypocrisy is love."Illuminating and delightful, this engaging book also provides a substantial portrait of one of the most influential of modern thinkers. Gathers some 800 quotations Drawn from the authoritative Princeton editions of Kierkegaard's writings Includes an introduction, a brief account and timeline of Kierkegaard's life, a guide to further reading, and an index"--